TANGGUNGJAWAB HUKUM KORPORASI YANG TERLIBAT TINDAK PIDANA KORUPSI - Piatur Pangaribuan; Aditya Dendi Darmawan (Fakultas Hukum Universitas Balikpapan, 2020)
Corruption practices occur in Indonesia not only involving individuals, but corruption involving a limited liability company. The purpose of this study is to determine law enforcement against corporations related to corruption and factors that influence the law enforcement of legal entities or corporations. Data analysis method used is normative analysis, researchers also conduct interviews, from the results of the study will be linked to existing rules. The issuance of PERMA RI No. 13 of 2016 concerning Procedures for Handling Criminal Cases by Corporations of accountability and law enforcement needs to be done. The law enforcement process for corruption cases that are sanctioned is only the director or commissioner of a legal entity that commits a criminal act of corruption but should the legal entity itself as well.